Integrated Postsecondary Education Data System (IPEDS): Fall Enrollment Analysis, 1990 ([Verlag nicht ermittelbar], 2003)
This collection contains two data files for the 1990 IPEDS Fall Enrollment survey. Part 1, Institutional Characteristics, contains the institutional characteristics data for all institutions by level of study, type and control of institution, affiliation, and offered degrees. Part 2, Enrollment Data by Race/Ethnicity, contains enrollment data by racial and ethnic background.